Interior space management strategies among selected flood-prone residences in Barangay Nangka, Marikina City - Barrozo, Nadine Andrea B.
This study explored how Filipino households manage their interior spaces to cope with recurring floods, identifying modifications, solutions, routines, and renovations applied after flooding events. It examined selected residents of Barangay Nangka in Marikina City, a low-lying community near a river and frequently affected by flooding. It aimed to document both common and unique strategies in a post-pandemic context, drawing from previous studies such as Turla (2021) and Garcia (2017) while identifying new strategies. Using a qualitative, descriptive case study approach, five households were selected through purposive and snowball sampling. Data were gathered through surveys, interviews, and participatory photographic documentation, then analyzed thematically. Findings revealed repeated damage to floors, ceilings, walls, electrical systems, and furniture. Respondents adopted a range of practical strategies such as using plastic furniture and opting for polished concrete finishes, alongside more unique solutions like ceiling-mounted storage, building a second floor with a kitchen, and creating buffer zones. The effectiveness of a strategy, as perceived by participants, was closely related to its practicality. Strategies that did not involve additional costs or that included low-cost measures received the highest ratings. Further, resource-intensive solutions were rated lower in effectiveness due to concerns about high costs and long-term maintenance. Financial limitations, ease of cleaning, health, and structural conditions heavily influenced choices. It was also found that participants developed a stronger understanding of material properties through experience. This study concludes that interior design supports flood resilience through practical, low-cost strategies, underscoring the value of empathy and context in designing adaptive living spaces.